RESEARCH ON MATERIALS USED IN THE CONSTRUCTION OF ARCHITECTURAL MONUMENTS (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Further comprehensive study of the structures of civil buildings erected in the late XIX and early XX centuries, included in the list of protection of architectural monuments of Bukhara and materials used in their construction, has great scientific and practical significance. This article presents the results of studying the architectural designs of some interesting monuments of Bukhara architecture, for the tourists mentioned above. The compressive strengths of bricks and masonry mortars used in the construction of foundations and walls of buildings were investigated.